Pengembangan Media Pembelajaran Interaktif untuk Meningkatkan Kreativitas Pembelajaran PKN Siswa Kelas V Sekolah Dasar - Fitriyani Fitriyani; Awalina Barokah; Bulan Kurniati (EduInovasi: Journal of Basic Educational Studies, 2023)
This research is motivated by the limited teaching materials in elementary schools and the lack of interactive learning media developed. This development research aims to produce a "Garudaku" board product and to find out the practicality and effectiveness of students towards the "Garudaku" board product in PKN subjects in grade V, so that the quality of learning at school is much more enjoyable and more able to hone students' abilities. in creative thinking. This study uses the type of learning design development research or RnD using the ADDIE model. The research subjects involved consisted of three experts (media experts, linguists and material experts) and fifth grade students. The results of this study resulted in the product "Garudaku" board which can be used to explain basic schooling as teaching materials for students who have meet the very good criteria with an average score of the three experts, namely 96.9% with the very feasible category and very practical criteria and the level of effectiveness with an average of 90% is in the very effective category. The teaching materials for the "Garudaku" board product are appropriate, practical and effective for use in Class V elementary school PKN learning. The development of interactive learning media is a solution for learning that involves students actively in the learning process. The purpose of this research is to create learning media to help increase creativity and interest in learning Citizenship Education (PKN). Keywords: Interactive Learning, Creativity, PKN, Elementary School